FINANCIAL STRATEGY IN DECISION MAKING FOR MARINA BUSINESS DEVELOPMENT IN BENOA BALI (CASE STUDY: PT. PELINDO PROPERTI INDONESIA) - Mahde Kumar; Fitri Ismiyanti (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
A company needs to determine the strategies that will be implemented by the company, after the strategy is set the company needs to consider the steps that must be taken so that the chosen strategy can provide added value to the company. Financial performance is one of the measuring tools that can be used in assessing the success of the strategy taken by the company and to know the amount of added value the strategy provides to the company's performance. Several financial indicators that can be used to determine financial performance such as NPV (Net Present Value), IRR (Internal Rate of Return), PP (Payback Period) and PI (Profitability Index) are indicators commonly used by companies, those are no exception for PT. Pelindo Properti Indonesia. PT. Pelindo Properti Indonesia (PT. PPI) is a subsidiary of PT. Pelabuhan Indonesia III (Persero). As a new company, PT. PPI needs to show good performance to its stakeholders, PT. BJTI and PT. Pelindo III, one of which is through a development strategy in the business division that contributes the most to the company, the Benoa Marina Bali business division. This research is a quantitative descriptive research and uses data collection through in-depth interviews and data processing by using financial indicators such as NPV, IRR, PP and PI. The results of the financial feasibility analysis on the development of marina in Benoa are feasible based on calculations on indicator of  NPV, IRR and PI. The payback period for Benoa marina development occurred in the 13th year of the 6th month. Based on the sensitivity test of funding combination using self capital and debt in the form of a shareholder loan, the most optimal combination is a combination of 50% equity and 50% debt.